Time, Temporality, Narrative and Identity in Three Works of Historiographic Metafiction - Liebenberg, Xanya (University of the Witwatersrand, Johannesburg, 2024)
This dissertation examines the ways in which concepts of identity and self-understanding cluster around notions of time and temporality in Salman Rushdie’s Midnight’s Children (1981), Peter Ackroyd’s Hawksmoor (1985), and Jonathan Safran Foer’s Everything Is Illuminated (2002). It argues that many theories of time neglect the uniquely human experience thereof, which finds expression in the intersection of time and narrative. Narrative is an inherently temporal process which functions as an epistemological tool through which we grapple with our embeddedness in time, and within the stories of others. The process of narrative identity formation, that is, of becoming, is explored from different perspectives in each text. In Midnight’s Children, identity is formed through intergenerational narratives and intersubjectivity. In Hawksmoor, the syncretic layering of Nicholas Dyer’s churches embodies the same syncretism which constitutes identity. Identity, in this novel, is made up of fragments and traces manifesting in different timelines. In Everything Is Illuminated, identity is formed through absences, loss, and silences which function as traces, negative spaces and Derridean cinders. Everything Is Illuminated also underscores the role of intersubjectivity and the co- creation of identity. Through patterning and repetition, each novel embodies a sense of time which rejects linearity. Furthermore, each novel foregrounds the temporal processes that infuse narrative by engaging with time and temporality thematically, as well as embodying these temporal processes in various ways throughout each text. Although all three texts are examples of historiographic metafiction, this dissertation concludes by suggesting that our understanding of the human experience of time, temporality and identity in other texts and genres may benefit from an approach which foregrounds the intersection between time and narrative
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Salman Rushdie; Peter Ackroyd; Jonathan Safran Foer; time; temporality; narrative; identity; historiographic metafiction; fragmentation; patterning; intersubjectivity; syncretism; trauma; SDG-4: Quality education